Vortioxetine attenuates the effects of early-life stress on depression-like behaviors and monoamine transporters in female mice. (15th March 2021) - Liu, Xiao; Sun, Ya-Xin; Zhang, Chen-Chen; Zhang, Xian-Qiang; Zhang, Yue; Wang, Ting; Ma, Yu-Nu; Wang, Han; Su, Yun-Ai; Li, Ji-Tao; Si, Tian-Mei
Abstract: Major depressive disorder is a major psychiatric disorder and a leading cause of disability around the world. Females have about twice as high an incidence of depression as males. However, preclinical animal models of depression have seldom investigated the molecular alterations associated with higher depression risk in females. In this study, adopting the early-life stress (ELS) paradigm of limited bedding and nesting material, we found that ELS induced depression-like behaviors only in adult female mice, as evaluated by sucrose preference and tail suspension tests. We then examined the ELS effects on monoamine neurotransmission (transporters for monoamine reuptake and release) in depression-related brain regions in female mice. We found that ELS resulted in widespread changes of the expression levels of these transporters in four brain regions. Moreover, systemic 21-day treatment with vortioxetine, a novel multimodal antidepressant, successfully reversed depression-like behaviors and normalized some molecular changes, including that of the norepinephrine transporter in the medial prefrontal cortex, vesicular monoamine transporter 2 in nucleus accumbens core, and serotonin transporter in amygdala. Collectively, these results provide evidence for the validity of using the limited bedding and nesting material paradigm to investigate sex differences in depression and demonstrate that the region-specific alterations of monoamine neurotransmission may be associated with depression-like behaviors in female mice. This article is part of the special issue on 'Stress, Addiction and Plasticity'. Highlights: Early-life stress (ELS) induced depression-like behaviors in female, not male, mice. ELS altered MAT and VMAT2 expression in depression-related brain areas in females. Vortioxetine reversed ELS-induced depression-like behaviors in female mice. Vortioxetine reversed ELS effects of mPFC-NET, NAc-VMAT2, and Amy-SERT in females.